Non-viviparous pre-dispersal seed germination in Amaranthaceae in the cold deserts of Central Asia - Lu, Juanjuan; Liu, Wenya; Han, Jincai; Tan, Dunyan; Baskin, Carol C.; Baskin, Jerry M. (Frontiers in Ecology and Evolution, 2022)
In the broad context of understanding the relationship between timing of seed germination and adaptation of a plant species to its habitat. The purpose of this study was to purse an observation of pre-dispersal seed germination of Salsola brachiata (Amaranthaceae) in late winter 2021 in the Amaranthaceae species-rich cold deserts in northwest China (Central Asia). We searched for pre-dispersal germination in species of Amaranthaceae growing in sand dunes (S), salt deserts (SD) and gravel deserts (GD). We examined 69 species in 155 populations in autumn 2021 and 52 species in 12 populations in early spring 2022. No seeds of any of the 69 species germinated on the mother plants in autumn 2021, while 30 of 52 species (57.7%) did so during snowmelt in early spring 2022. The rank order of species with few to many seeds germinated on the mother plants was annuals (66.7 %) > small shrubs (23.3 %) > small trees (6.7 %) > shrubs (3.3 %). The number of species in S, SD and GD with pre-dispersal germinated seeds was 16 of 27 (59.3 %), 15 of 31 (48.4 %) and 15 of 30 (50.0 %), respectively. The high species occurrence of pre-dispersal germination in early spring suggested that it might be adaptive in the unpredictable-rainfall growing-season environment of the cold deserts of Central Asia, a center of diversity of Amaranthaceae. However, preliminary studies on seedling/juvenile survival of S. brachiata showed that those from post-dispersal soil-germinated seeds had the best survival, suggesting that pre-dispersal seed germination may be maladaptive.